(untitled) (Gaceta Técnica, 2023)
The quality control of a fill is generally performed with standardized methods, such as the sand cone and the nuclear densimeter, but an alternative method, the dynamic cone penetrometer, is being proposed and is usually used to calculate the in situ California bearing ratio. In this investigation, the dynamic cone penetrometer was used to perform quality control of a silty clayey gravel soil with sand. First, the material was characterized, basic and specific tests were carried out, and a 12,00m long test fill was made, divided into seven zones, compacted with different energies, and sand cone and dynamic cone penetrometer tests were carried out. With the data obtained, a correlation equation was determined, where the dynamic cone penetrometer index was the independent variable and the dry density the dependent variable. With the equation we proceeded to calculate the dry density of a compacted platform with a single test energy of 2,40x2,40m, a good correlation was estimated between the compacted dry density and the dynamic cone penetrometer index, thus showing the possibility of its use in the quality control of a granular backfill. In the comparison of the dry density calculated from the correlation equation and the density found with the sand cone, it was observed that it varies around 6%